The Effect of Assertiveness Training on Social Emotional Learning Skills of Secondary School Students - Mehmet Akif DEMIRELLI (Muhammed Yıldız, 2020)
In this research, the effect of Assertiveness Training applied to secondary school students on social and emotional learning skills of students was investigated. 25 (13 female - 12 male) experimental group, 25 (13 female - 12 male) control group, totally 50 secondary school students participated in this research. The announcement of the training was made with the posters in the schools and the students applied for the education voluntarily. Experimental design was used in the research. The students participated in Assertiveness Training consisted of 10 sessions. The Social Emotional Learning Skills Scale (SDQAS) was used to measure participants' social and emotional learning skills. In order to analyze the pretest points of the experimental and control groups, t test was used for independent samples and after the application, to analyze the difference of pretest-posttest scores of the experimental and control groups dependent samples t test was also used. As a result, while assertiveness training significantly influenced students' social and emotional learning, communication skills and stress levels, it had no significant effect on their problem solving and self-perceptions.